Transcriptome time-course analysis unravels the regulatory networks governing ratooning decline in sugarcane - Zhang, Sisi; Zhao, Feiyan; Yang, Zongtao; Yang, Ting; Li, Yanye; Zhang, Zhongfu; Wu, Jianming; Liu, Jiayong; Deng, Jun; Zhao, Yong; Zhang, Yuebing (Frontiers in Plant Science, 2026)
IntroductionRatooning cultivation is the predominant production mode for sugarcane, yet ratooning decline represents a critical constraint limiting high and stable yields. To elucidate the molecular mechanisms underlying this phenomenon, this study aimed to reveal the critical period of sugarcane ratooning decline and variety-specific regulatory networks by integrating multi-year field yield data with transcriptome analysis.MethodsThis study combined five consecutive years of field yield data (from plant cane to the fourth ratoon, PC–R4) with root time-course transcriptome data from three sugarcane varieties (YT93-159, YZ05-51, and YZ08-1609). Differentially expressed genes (DEGs) were identified, followed by Mfuzz time-course clustering, Weighted Gene Co-expression Network Analysis (WGCNA) to pinpoint key gene modules and hub genes, with validation by qRT-PCR.ResultsThe study revealed that the R2-R3 transition represents the critical turning point for ratooning decline. Compared to second ratoon (R2), yields of the three varieties decreased significantly by 14.3%, 12.64%, and 9.45% (P < 0.05), respectively, in R3 (third ratoon). Based on this critical period, comparative analysis between R3 and R2 identified 11,348, 20,638, and 21,977 differentially expressed genes (DEGs) associated with ratooning decline in the three varieties, respectively.Five highly overlapping gene modules (overlap rates: 48%–100%) were identified, yielding 25 hub genes, of which 15 exhibited peak expression during R3. These hub genes coordinately constitute a regulatory network encompassing energy metabolism, signal transduction, protein homeostasis, and defense responses. Notably, different varieties exhibited specific response pathways: YT93-159 specifically upregulated galactinol synthase (GOLS) to enhance osmotic adjustment; YZ05-51 primarily relied on thiosulfate sulfurtransferase (STR) to maintain cellular redox homeostasis; and YZ08-1609 upregulated ubiquitin ligase and proteasome subunit genes to strengthen protein quality control.DiscussionThis study identifies the R2-R3 transition as the critical period of ratooning decline and uncovers variety-specific coping mechanisms at the molecular level. Different varieties exhibited distinct response pathways within the regulatory network, suggesting genotype-dependent adaptation strategies to ratooning stress. The key hub genes revealed here offer valuable molecular targets and genetic resources for breeding strong-ratooning sugarcane varieties, providing insights for improving sugarcane ratooning performance and sustainability.